High-frequency microwave ablation method for enhanced cancer treatment with minimized collateral damage - Yoon, Jeonghoon; Cho, Jeiwon; Kim, Namgon; Kim, Dae-Duk; Lee, Eunsook; Cheon, Changyul; Kwon, Youngwoo (WILEY, 2011)
To overcome the limits of conventional microwave ablation, a new frequency spectrum above 6 GHz has been explored for low-power and low collateral damage ablation procedure. A planar coaxial probe-based applicator, suitable for easy insertion into the human body, was developed for our study to cover a wideband frequency up to 30 GHz. Thermal ablations with small input power (1-3 W) at various microwave frequencies were performed on nude mice xenografted with human breast cancer. Comparative study of ablation efficiencies revealed that 18-GHz microwave results in the largest difference in the temperature rise between cancer and normal tissues as well as the highest ablation efficiency, reaching 20 times that of 2 GHz. Thermal profile study on the composite region of cancer and fat also showed significantly reduced collateral damage using 18 GHz. Application of low-power (1 W) 18-GHz microwave on the nude mice xenografted with human breast cancer cells resulted in recurrence-free treatment. The proposed microwave ablation method can be a very effective process to treat small-sized tumor with minimized invasiveness and collateral damages.
Keywords: DIELECTRIC-PROPERTIES; PERMITTIVITY; UNCERTAINTY; CARCINOMA